(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Physical and mental health are significantly related to adequate sleep and sleep satisfaction. Sleeping disorder is one of the most severe occupational risks for modern firefighting services. Thus, the current study was conducted to evaluate sleep quality and its effective factors in firefighters‏. Methods: This descriptive-analytical study was carried out among all firefighters in Shahroud, Iran, in 2017. All data were collected by a two-part questionnaire containing demographic information and the Pittsburgh Sleep Quality Index (PSQI), which was completed while interviewing the participants. Finally, data were analyzed by SPSS software. Results: PSQI was obtained as 7.65±2.98, which classified into "Low Quality." Sleep latency, sleep duration, sleep disturbances and day-time dysfunction had a significant relationship with sleep quality (P<0.05). Moreover, the results demonstrated that PSQL score had a strong relationship with age and BMI (F-model= 21.78 and P<0.001 and r=0.701). Conclusions: Results of this study showed that firefighters have not adequate sleep quality. It is suggested to participate young people in missions since their sleep quality was better. Also, weight loss is suggested for overweight people in order to improve their sleep quality‏.